The Hunger games. Mockingjay. Part 2 [videorecording (DVD)] - Lawrence, Jennifer, 1990-; Hutcherson, Josh; Hemsworth, Liam, 1990-; Harrelson, Woody; Banks, Elizabeth, 1974-; Hoffman, Philip Seymour, 1967-2014; Sutherland, Donald, 1935-; Collins, Suzanne (Lionsgate, 2016)
Katniss realizes the stakes are no longer just for survival; they are for the future. With the nation of Panem in a full scale war, Katniss confronts President Snow in the final showdown. Teamed with a group of her closest friends; including Gale, Finnick and Peeta; Katniss goes off on a mission with the unit from District 13 as they risk their lives to liberate the citizens of Panem, and stage an assassination attempt on President Snow who has become increasingly obsessed with destroying her.